Use of follow-on fingolimod for multiple sclerosis: Analysis of effectiveness and patient reported outcomes in a real-world clinical setting - SÜNTER, GÜLİN (My University, 2023)
Background: Follow-on disease modifying therapies (FO-DMTs) do not always require Phase III studies. There are concerns that cheaper FO-DMTs are only used to reduce healthcare costs. However, the well-being of people with MS (pwMS) should be a priority. We aimed to evaluate the efficacy, safety and treatment satisfaction of one of the FO- Fingolimod (FTY) used in Turkey with the approval of Turkish Ministry of Health. Methods: PwMS under FTY were recruited from 13 centers and real-world data and answers of satisfaction and adherence statements of pwMS on FTY treatment were analyzed. Results: Data of 239 pwMS were obtained. The duration of FTY treatment was 2.5 ± 0.8 (1–4) years in pwMS who were included in the study and whose treatment continued for at least one year. Significant decreases in annual relapse rate (p < 0.001), Expanded Disability Status Scale (p < 0.001) and neuroimaging findings (p < 0.001) were observed. While 64% of the patients were satisfied and 71.5% were found to adherent with this FO-FTY. Conclusion: This multicenter retrospective study found that the efficacy, safety and treatment adherence of a prescribed FO-FTY were consistent with the results of real-world studies. Studies including real-world data may provide guidance to address issues related to FO-FTY use.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Yaşam Bilimleri; Nöroloji (klinik); Life Sciences; Neurology (clinical); Adherence; Efficacy; Follow-on drug; Generic fingolimod; Real-world data; Safety; Satisfaction